The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1073/pnas.1300314110
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory monocytes are potent antitumor effectors controlled by regulatory CD4+T cells

Abstract: The present study evaluates the impact of immune cell populations on metastatic development in a model of spontaneous melanoma [mice expressing the human RET oncogene under the control of the metallothionein promoter (MT/ret mice)]. In this model, cancer cells disseminate early but remain dormant for several weeks. Then, MT/ ret mice develop cutaneous metastases and, finally, distant metastases. A total of 35% of MT/ret mice develop a vitiligo, a skin depigmentation attributable to the lysis of normal melanocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 47 publications
4
49
0
1
Order By: Relevance
“…15 Our study revealed a direct correlation between the amplification of this subset within the spleen and the tumor microenvironment and tumor extension (Fig. 2E).…”
Section: Foxp3supporting
confidence: 52%
“…15 Our study revealed a direct correlation between the amplification of this subset within the spleen and the tumor microenvironment and tumor extension (Fig. 2E).…”
Section: Foxp3supporting
confidence: 52%
“…Studies of Smyth line chickens, an animal model for human autoimmune vitiligo, have demonstrated that elevated leukocyte infiltration in early and active vitiligo is accompanied by increased levels of cytokine expression, especially in interferon (IFN)-IL-10, and IL-21 [68]. Recently, in a mouse model of spontaneous melanoma, Treg cell-depletion and IL-10 neutralisation led to an increased occurrence of vitiligo which correlated with a decreased incidence of melanoma metastases [69].…”
Section: Interleukin-10mentioning
confidence: 99%
“…Clustering of cell surface VCAM-1 triggered Akt activation and protected cancer cells from pro-apoptotic cytokines such as TRAIL. However, anti-metastatic functions of inflammatory monocytes have also been reported [94]. In a mouse model of spontaneous melanoma expressing human RET oncogene, CD11b+ Ly6C high monocytes inhibited tumor cell proliferation through a reactive oxygen species-dependent mechanism.…”
Section: Tumor-associated Myeloid Cells (Tamcs)mentioning
confidence: 99%